Comparative Evaluation of the Echocardiographic Parameters of Dogs with Chronic Mitral Valve Regurgitation Treated with Amlodipine or Pimobendan - Kamakura, Orson Nobumitsu; Goldfeder, Guilherme Teixeira; Itikawa, Paula Hiromi; Larsson, Maria Helena Matiko Akao (Acta Scientiae Veterinariae, 2017)
Background: Chronic mitral valve regurgitation is the most common heart disease in dogs. It is caused by myxomatous mitral valve degeneration, an acquired degenerative disease that can lead to congestive heart failure. Pimobendan is a mixed action drug, with inotropic and vasodilator proprieties, widely used to treat such dogs. Amlodipine is a pure vasodilator drug used as an anti-hypertensive agent, with no inotropic effects. This study aimed to compare echocardiographic, electrocardiographic and blood pressure parameters between dogs with congestive heart failure treated with pimobendan and those treated with amlodipine in addition to conventional therapy. Materials, Methods & Results: A prospective, randomized, double-blind study was conducted in dogs with stage C chronic mitral valve regurgitation according to the 2009 American College of Veterinary Internal Medicine (ACVIM) guidelines, who weighed up to 15 kg. Randomization was performed using appropriate software and the sealed envelope technique. Blinding of the owner, the main researcher, and the person who performed the clinical analysis was guaranteed by the use of identical capsules and bottles for both pimobendan and amlodipine. Statistical analysis was performed using specialized software. Eligibility was determined by predefined inclusion and exclusion criteria. Dogs with cardiac disease other than mitral and/or tricuspid degeneration, patients already undergoing pharmacological treatment with drugs other than enalapril and furosemide, patients with systolic blood pressure below 100 mmHg, patients with chronic kidney disease in stages III or IV according to International Renal Interest Society staging system for chronic kidney disease (2009), and patients with other systemic debilitating diseases were excluded from the study. The animals were randomized into two groups based on the drug they received. Group A received pimobendan (n = 10) and group B received amlodipine (n = 11). All animals were also treated with furosemide and enalapril maleate and evaluated three times over a period of sixty days (T0, T30, T60). Changes in echodopplercardiographic and electrocardiographic parameters and systolic blood pressure were investigated. There were no significant differences in electrocardiographic parameters or systolic blood pressure between the groups at any time. Among the echocardiographic parameters, only early diastolic myocardial peak velocity (Em) and late diastolic myocardial peak velocity (Am) showed a significant difference between groups. Discussion: This was the first prospective randomized double-blind study comparing pimobendan and amlodipine in the treatment of dogs with stage C chronic mitral valve regurgitation according to the ACVIM consensus statement. The use of pimobendan in these patients has been debated because myocardial inotropism is generally preserved in them. Some authors argue that early use of the drug can even lead to deleterious effects on the heart. In the present study, the groups showed no statistically significant differences in systolic blood pressure or electrocardiographic parameters. Among the echocardiographic parameters, statistically significant differences were only observed in the speed of Em waves between groups at T0, in the speed of Em waves in the amlodipine group between T0 and T60 times, and in the speed of Am waves in the amlodipine group between T30 and T60 times. Both parameters are indices of diastolic function and may indicate a change in early myocardial relaxation. From the findings of this study, we could not conclude whether one drug was superior to the other.